An Analysis of the Effects of Monetary Policy and Price Stability on the Economic Growth of South Africa - Munzhedzi, Vusani; Ratombo, Ndivhuho Eunice (International Journal of Economics and Financial Issues, 2025)
Economic growth is regarded as one of the key determinants which is utilized by developed and developing countries to measure economic activities success through Gross Domestic Product (GDP). The purpose of this study was to investigate the effects of monetary policy and price stability on the economic growth of South Africa from 1997 to 2023. South Africa is failing to meet its inflation goals, for instance, in the last decade it missed five times of opportunities, which raises concerns about the efficiency of using inflation targeting as a monetary policy framework to achieve price stability and sustainable economic growth. Time series data was used, sourced from the World Bank data platform. The autoregressive distributed lag (ARDL) technique was used based on the unit root test outcomes which display a mixture of I (0) and I (1) on variables. The findings showed that money supply, inflation, and exchange rate are negatively related to GDP growth while interest rate reveals a positive influence towards economic growth in the long run. This study has contributed to the academic literature by providing an in-depth analysis of how different aspects of monetary policy, specifically money supply and interest rates affect economic growth in South Africa.